Respostas
respondido por:
0
A3 = 10 e A6 = 7
A3 = A1 + 2r e A6 = A1 + 5r
Isolando A1 nas duas equações:
A1 = A3- 2r e A1 = A6- 5r
Podemos igualar então:
A3- 2r = A6- 5r
10-2r=7-5r
10-7=5r+2r
3=7r
r=3/7
Qualquer dúvida pode perguntar.
A3 = A1 + 2r e A6 = A1 + 5r
Isolando A1 nas duas equações:
A1 = A3- 2r e A1 = A6- 5r
Podemos igualar então:
A3- 2r = A6- 5r
10-2r=7-5r
10-7=5r+2r
3=7r
r=3/7
Qualquer dúvida pode perguntar.
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás